Wear of different PVD coatings at industrial fine-blanking field tests - Liina Lind; Priidu Peetsalu; Fjodor Sergejev (Medžiagotyra, 2015)
Thin hard physical vapor deposited (PVD) coatings play significant role on wear performance of fine-blanking punches in the presence of extremely high contact stresses. Nevertheless it seems that in blanking or fine-blanking the coatings are selected based on coincidence, trial-error-method or latest trends. There is limited information about planning and conducting the fine-blanking industrial field tests and measuring the wear of different coatings. In the present study a set of fine-blanking punches and laboratory specimens were prepared with three coatings – TiCN, nACRo and nACo. As substrate material Böhler S390 Microclean high speed steel was used. Coating mechanical properties (modulus of elasticity and nanohardness) were measured and wear rate with alumina ball was determined using the reciprocating sliding test. Wear of coatings was measured from punches after industrial use. All of the tested coatings showed high variance of wear. However coatings nACo and nACRo have better average wear resistance in fine-blanking compared with the well-known TiCN. Industrial field tests show correlation to the ratio elastic strain to failure H/E. DOI: http://dx.doi.org/10.5755/j01.ms.21.3.7249